Effect of Pets on Human Behavior and Stress in Disaster - Tanaka, Aki; Saeki, Jun; Hayama, Shin-ichi; Kass, Philip H. (Frontiers in Veterinary Science, 2019)
Animal components were not clearly defined in disaster preparedness planning in Japan at the time of the earthquakes in 2011. Evacuation failure was quite common due to pet ownership in this disaster. Public attention to the welfare of affected animals in this disaster triggered an awareness of the importance of taking care of animals during disasters. However, research on human behavior towards pets or effect of pets on human during disasters was sparse. Posttraumatic stress disorder (PTSD) scores among pet-owners and non-pet owners in disaster were compared and attitudes towards pets were evaluated in this study. A questionnaire was distributed, and interview performed to attendees at an annual animal welfare event. The Japanese-Language Version of the Impact of Event Scale-Revised was used to evaluate PTSD from the disaster. PTSD score was higher in pet-owners compared to non-pet owners immediately after the earthquakes, but it was lower in pet-owners compared to non-pet owners 4.4 years post-disaster. Most people considered pets should evacuate with people, although, less than half of non-pet owners did not agree to have animals co-located at evacuation center. In order to enhance safety and security of both human and animals at evacuation centers, it is important to address animal issues and include animal considerations in disaster preparedness planning in advance. Pets were regarded as risk factors for human health and safety during the disaster; however, this study suggest pets may play important role as a protective factor for disaster victims.